(3GdHOjY aj eYQaI eG QSe aj eUMa YKeGf Hf YaGfs - (3GdbQWHj , eMeO Hf jhSa Hf jhSa Hf CMeO Hf eYGP GdLgfj GdCfOdSj, CHh YHO Gddg,J (B407 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bQi Ydi Ci YHO Gddg eMeO Hf jhSa Hf CMeO GdLgfi hbQCJ Ydjg ai SfI s
(3BNQgG (B:s
(3eeG GSJZfi WGdH GdbQBf eYQaJg HGdhbha Ydjg heG MLGg GdfMhjhf hGdbQGA s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B148 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B122s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs